2008
DOI: 10.1080/15250000701779386
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Effects of Variation in Infant Speech Segmentation: Influences of Word Familiarity

Abstract: Previous studies have shown that 7.5-month-olds can track and encode words in fluent speech, but they fail to equate instances of a word that contrast in talker gender, vocal affect, and fundamental frequency. By 10.5 months, they succeed at generalizing across such variability, marking a clear transition period during which infants' word recognition skills become qualitatively more mature. Here we explore the role of word familiarity in this critical transition and, in particular, whether words that occur fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 13 publications
(32 reference statements)
2
30
0
Order By: Relevance
“…Thus, we would expect that children with more extreme problems in orienting will have more severe social-communicative symptoms. Poor orienting and defensive reactions may be associated with extreme states of physiological arousal, which have been linked to decreased perceptual and contingency learning in bobwhite quail neonates (Markham, Toth & Likliter, 2006) and premature human infants (Haley, Grunau, Oberlander, & Weinberg, 2008), respectively.…”
Section: Developmental Framework For Possible Links Between Sensory Responses and Social Communication And Language Functioning In Childrmentioning
confidence: 99%
“…Thus, we would expect that children with more extreme problems in orienting will have more severe social-communicative symptoms. Poor orienting and defensive reactions may be associated with extreme states of physiological arousal, which have been linked to decreased perceptual and contingency learning in bobwhite quail neonates (Markham, Toth & Likliter, 2006) and premature human infants (Haley, Grunau, Oberlander, & Weinberg, 2008), respectively.…”
Section: Developmental Framework For Possible Links Between Sensory Responses and Social Communication And Language Functioning In Childrmentioning
confidence: 99%
“…This is demonstrated by their early ability to recognize highly familiar items even when embedded in a stream of speech (Bortfeld, Morgan, Golinkoff, & Rathbun, 2005; Mandel-Emer, 1997; Singh, Nestor, & Bortfeld, 2008). Over the coming weeks, they become increasingly attuned to patterns of their native language, so that by about 7.5 months of age they can recognize newly familiarized monosyllabic words within fluent speech (Jusczyk & Aslin, 1995) and even certain types of bisyllabic words (Jusczyk, Houston, & Newsome, 1999).…”
Section: Early Word Recognition May Be Stress-fullmentioning
confidence: 99%
“…For instance, Jusczyk and Aslin (1995) found that 7.5-month-olds resemble adults in that they can recognize familiarized words in fluent speech and do not false alarm to items differing by only a single phonetic feature from familiarized targets. Subsequent studies have shown, however, that infants’ word recognition can be disrupted by changes in dimensions that would be lexically irrelevant to adults, such as talker gender (Houston & Jusczyk, 2000), speaker affect (Singh, Morgan, & White, 2004), or pitch (Singh, White, & Morgan, 2008). A range of studies have shown that infants rely heavily on lexical stress (i.e., when the syllables of a multisyllabic word are not stressed equally) for assistance in spoken word recognition, a factor that influences adult lexical processing as well (Cutler & Butterfield, 1992; Cutler & Norris, 1988; Mattys & Samuel, 1997; Norris, McQueen, & Cutler, 1995; Slowiaczek, 1990; Small, Simon, & Goldberg, 1988).…”
Section: Early Word Recognition May Be Stress-fullmentioning
confidence: 99%
“…For example, highly frequent lexical items such as ‘Mommy’ are easy for infants to detect in continuous speech (Bortfeld, Morgan, Golinkoff, & Rathbun, 2005; Singh, Nestor, & Bortfeld, 2008). Previous learning of stress patterns also influences segmentation skills: infants more readily segment unfamiliar words if they match the predominant stress pattern in the native language (Houston, Santelmann, & Jusczyk, 2004; Johnson & Jusczyk, 2001; Thiessen & Saffran, 2003), and shift their segmentation strategy based on exposure to novel stress patterns (Thiessen & Saffran, 2007).…”
Section: Introductionmentioning
confidence: 99%